CONFRONTING DIAGNOSTIC AND THERAPEUTIC CHALLENGES IN VIRAL REACTIVATION AFTER ALLOGENEIC TRANSPLANTATION: EXPERIENCE OF A BRAZILIAN PUBLIC CENTER - Campos, Sarah Emanuelle Viana; Barroso , Karine Sampaio Nunes; Leitão , João Paulo de Vasconcelos; Araújo , Beatriz Stela Gomes de Souza Pitombeira; Gurgel, Lívia Andrade; Alencar, Rafael da Nóbrega; Duarte, Fernando Barroso (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
BACKGROUND. Despite recent advances of allogeneic hematopoietic stem cell transplantation (HSCT), viral infections are still a significant complication and remain a frequent cause of morbidity. OBJECTIVE. To evaluate the profile of viral infection in patients undergoing HSCT in a Brazilian reference hospital. STUDY DESIGN. This is a retrospective, descriptive, analytical and quantitative study. Allogeneic transplants performed in the last 5 years, in patients aged 16 years or older, were analyzed. RESULTS. A total of 117 allo-HCT recipients were included. Of these, 50.43% were women and 49.57% were men, with a median age of 36 years. Acute myeloid leukemia was the most frequent underlying disease (27,35%). 88,33% of the patients had some virus detected (in any value) during the post-BMT period. There was a prevalence of viral reactivation in haploidenticals, with 90.91% of detection. CMV reactivation was the most frequent. We found a prevalence of CMV infection after allo-HSCT (70.94%) with 62 patients (52.99%) above the cut-off of 1,000 IU/mL and 21 (17.95%) below this value. EBV was the second virus with the highest reactivation rate. CONCLUSIONS. CMV remains in the first place among viral reactivations. CMV and EBV were predominant in unrelated transplants, while BKV and HHV6 predominated in haploidentical.